Australia's Foreign Relations with Pacific Countries in the Economic Sector for the 2012-2018 Period - Nuralfi Nazmi Laila (UIN Sunan Gunung Djati, 2020)
Relations between Australia and the Pacific countries occur because of the close geographical location and see the positive impact that can be caused by the collaboration. The purpose of this journal is to provide knowledge to the general public about how the application of international relations between Australia and the Pacific Country in the economic field. The method used in obtaining data is descriptive method. There is some cooperation in the field of economics conducted by Australia towards Pacific Countries, namely PSDI, PBIF, etc. Besides aiming to build diplomatic relations with the Pacific Country, Australia also intends to improve the quality of the economy that is in the Pacific Country. One of the ways in which Australia is doing is providing funding to the Pacific Country and improving the quality of existing human resources.